UCTAS : the UCT anaesthetics simulator : simulating the uptake and distribution of halothane - Cooper, Robin Andrew (Department of Medicine, 2023)
An anaesthetic simulator program that runs on an IBM personal computer system has been developed. The program allows an operator to observe the uptake and distribution of the volatile anaesthetic agent halothane by a standard 75kg patient. The "patient's" breathing is assisted by a ventilator and the anaesthetic gas is supplied through a simulated circle breathing circuit. The most important component of a simulator is a mathematical model of the system being simulated. In this case a model of the uptake and distribution of the anaesthetic agent halothane by the human cardiovascular and respiratory systems was required. Such a model was developed by combining features of several existing non-linear multi-compartmental models and adapting the equations to allow them to be implemented on a digital computer. The simulator software that was developed allows an operator to adjust physical parameters such as fresh gas flow rate, halothane concentration, and breathing parameters from the keyboard of an IBM PC computer and observe the way various model parameters respond on a graphics screen. The speed of the simulation is adjustable. i.e., the state of the model can be repetitively calculated and displayed at 1, 10, or 60 second intervals. Model parameters can be displayed in bar graph or line-graph form and may also be dumped to a text file for use by other plotting programs. The software package developed should provide a useful teaching aid to understand the distribution of patient.